Frontiers in Optics + Laser Science 2022 (FIO, LS) 2022
DOI: 10.1364/fio.2022.jtu5a.29
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Aspects of Optical Beam Shifts

Abstract: We indicate the possible expansion of the domain of optical beam shits to demonstrate exotic physical effects, such as, demonstration of joint correlation of the beam shifts, and mimicking PT symmetric systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…8 Although the shifts are of fundamentally different origin, we have recently shown that the beam shifts are inherently non-separable, and such non-separability becomes tangible only in certain regions of the corresponding parameter space. 9 In this work, we experimentally demonstrate the realization of this non-separability as a position-position classically entangled state by taking a polarized Gaussian beam reflected from an air-glass interface as a a tunable position-position classically entangled state. We anticipate that the manifestation of discussed entanglement will evident in a wide-range of light-matter interactions due to the ubiquitous nature of the beam shifts.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 Although the shifts are of fundamentally different origin, we have recently shown that the beam shifts are inherently non-separable, and such non-separability becomes tangible only in certain regions of the corresponding parameter space. 9 In this work, we experimentally demonstrate the realization of this non-separability as a position-position classically entangled state by taking a polarized Gaussian beam reflected from an air-glass interface as a a tunable position-position classically entangled state. We anticipate that the manifestation of discussed entanglement will evident in a wide-range of light-matter interactions due to the ubiquitous nature of the beam shifts.…”
Section: Introductionmentioning
confidence: 93%
“…We have recently used the Pearson correlation coefficient to quantify the non-separability of the longitudinal and transverse shifts. 9 As apparent from, 9 the non-separability although inherent in the formalism of the beam shifts, is only be detectable at certain regions of the corresponding experimental parameter space. For horizontal input polarization state, non-separability becomes noticeable for angles of incidence near θ i → Brewster's angle.…”
Section: Position-position Classical Entanglement From Optical Beam S...mentioning
confidence: 99%